Small RNA deep sequencing reveals full-length genome of Citrus yellow vein clearing virus in Chongqing, China - Yun-qi YU; Qiong WU; Hua-nan SU; Xue-feng WANG; Meng-ji CAO; Chang-yong ZHOU (Journal of Integrative Agriculture)
To identity the potential pathogen associated with the yellow vein clearing symptom on lemon trees, the profiles of virus-derived small interfering RNAs from citrus samples were obtained and analyzed by deep sequencing method in this study. Twenty-seven contigs almost cover the full length genome of Citrus yellow vein clearing virus (CYVCV) isolate YN were obtained using the small RNA deep sequencing technology. Analysis showed that this isolate CQ shared the highest nucleotide identity with isolate Y1 (JX040635) and YN (KP313242), both of which belong to the genus Mandarivirus in the family Alphaflexiviridae. Mapping analysis of viral-derived siRNA (vsiRNA) profiles revealed an uneven distribution pattern of their generations along both positive and negative genome strands, and 22- and 21-nt vsiRNAs ranked the majority. BLAST against viroids and other viral databases confirmed that this sample was single-infected only by CYVCV, which indicated that CYVCV was the exact causal agent for the yellow clearing symptom occurring on lemon. This is the first CYVCV isolate detected in Chongqing and the second in China. This result could provide a molecular basis for the investigation of citrus viral diseases to protect citrus health in this region.